Comparison of the Number of Dog Adoptions in a Pilot Program That Restored Limited Visitor Access to Kennels: A Community Case Report - Mavrovouniotis, Michael Loizos (Journal of Shelter Medicine and Community Animal Health, 2024)
In the 2020–2022 pandemic period, the Orange County (California) animal shelter used an appointment-based adoption system in which visitors did not have access to the kennels. In a 2023 pilot program, visitors were allowed to view some large dogs in their kennels for a limited portion of the shelter’s hours of operation. More adoptions than expected were observed during viewing hours compared to other days and times during the pilot period. Compared to the same calendar period in the preceding year, kennel viewing periods showed an 82% increase in adoptions while appointment-only periods showed only a 4% increase. A higher proportion of large dogs were adopted from the viewable kennels than from the general inventory of large dogs. This was not a randomized controlled study, and these estimates are based solely on retrospective comparisons. It is not known how these increased adoption levels scale if access is available to more kennels or for a substantial portion of the hours of operation.